2011
DOI: 10.1002/pon.2020
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of QUICATOUCH: a computerised touch screen evaluation for pain and distress in ambulatory oncology patients in Newcastle, Australia

Abstract: The QUICATOUCH assessment for pain and distress was implemented into usual clinical practice with reasonable coverage of patients for modest cost. It was effective in monitoring the patients over time, contributed to a reduction in pain and distress, whilst appropriately increasing the number of new patients reaching psychological treatment as part of the clinical service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…Physical symptoms also coincided with increasing psychosocial function decline associated with head and neck treatment weeks 3 and 4, including eating, speech, sexual, and dental problems . Similarly, pain was associated with psychosocial function decline consensually in four studies without being refuted. In summary, physical side effects are a well‐supported risk factor associated with psychosocial function decline.…”
Section: Discussionmentioning
confidence: 91%
“…Physical symptoms also coincided with increasing psychosocial function decline associated with head and neck treatment weeks 3 and 4, including eating, speech, sexual, and dental problems . Similarly, pain was associated with psychosocial function decline consensually in four studies without being refuted. In summary, physical side effects are a well‐supported risk factor associated with psychosocial function decline.…”
Section: Discussionmentioning
confidence: 91%
“…Comparison of these data with similar studies is made difficult by differing methodologies and study compositions. One study of early breast cancer patients reported rates of CES‐D depression (≥16) as 40.9% around diagnosis and 27.8% 12 months later .…”
Section: Discussionmentioning
confidence: 99%
“…Oncology and haematology outpatients completed the DT, PL and other measures on a touchscreen computer (QUICATOUCH) prior to their oncology appointment. Details of the QUICATOUCH assessment and scoring algorithms have been described previously [18][19][20].…”
Section: Settingmentioning
confidence: 99%